2023
DOI: 10.1186/s12884-023-05855-4
|View full text |Cite|
|
Sign up to set email alerts
|

Psychometric evaluation of the postpartum specific anxiety scale – research short-form among Iranian women (PSAS-IR-RSF)

Abstract: Background The increasing prevalence of postpartum anxiety as a common psychological problem affects a large part of women’s lives. Despite the existence of tools in this field, but due to the lack of specificity in reflecting postpartum anxiety, it is necessary to have a specific tool to screen it. Since the psychometric evaluation of the Postpartum Specific Anxiety Scale-Research Short-Form (PSAS-RSF) among Iranian women has not been assessed in Iran until now, so we decided to conduct this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The PSAS was originally developed as an English-language tool [ 20 ] and contains these four factors: maternal competence and bonding anxieties (15 items), infant safety and welfare anxieties (11 items), practical infant care anxieties (7 items), and psychosocial adjustment to motherhood (18 items). To date, there have been two derivative short-form research studies [ 38 , 39 ], and the tool has been translated and validated in French [ 40 ], Spanish [ 41 ], Chinese [ 42 ], Persian [ 43 ], and Italian [ 14 ], the latter of which has been used in this study. The scale showed good internal consistency (Cronbach’s α = 0.94).…”
Section: Methodsmentioning
confidence: 99%
“…The PSAS was originally developed as an English-language tool [ 20 ] and contains these four factors: maternal competence and bonding anxieties (15 items), infant safety and welfare anxieties (11 items), practical infant care anxieties (7 items), and psychosocial adjustment to motherhood (18 items). To date, there have been two derivative short-form research studies [ 38 , 39 ], and the tool has been translated and validated in French [ 40 ], Spanish [ 41 ], Chinese [ 42 ], Persian [ 43 ], and Italian [ 14 ], the latter of which has been used in this study. The scale showed good internal consistency (Cronbach’s α = 0.94).…”
Section: Methodsmentioning
confidence: 99%
“…The English-language PSAS has been subject to modification first as a 12-item research short-form for use in global crises [PSAS-RSF-C; ( 30 )] developed during the pandemic; and also as a 16-item research short-form [PSAS-RSF; ( 31 )]. The scale has also received broad global interest and approved translations have been published in Chinese [PSAS-CN; ( 32 )], Persian [PSAS-IR; ( 33 ), PSAS-IR-RSF; ( 34 ), PSAS-IR-RSF-C; ( 35 )], French [PSAS-FR; ( 36 )]; and Spanish [PSAS-ES; ( 37 )]; with other translations currently ongoing in Brazilian Portuguese, Dutch, Palestinian Arabic, amongst others. In each country, the PSAS demonstrated good acceptability, validity and test–retest reliability.…”
Section: Introductionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported an error in Table 3 in PDF proof. Table 3 in the PDF version contains incomplete details, but HTML version contains complete details.…”
mentioning
confidence: 99%